An overview of research within the Genre and Multimodality framework. (December 2017) - Hiippala, Tuomo
Abstract: This review article provides an overview of the research conducted within the Genre and Multimodality framework, which has been used to describe the multimodality of page-based documents and other multimodal artefacts over the past 15 years. The article explicates the motivation and inspiration for developing the framework, introduces its central theoretical concepts and presents its applications across a number of case studies. Finally, the article discusses the criticism directed towards the model and identifies avenues of future development.